A preliminary assessment of the deep-sea Decapoda collected during the KARUBENTHOS 2015 Expedition to Guadeloupe Island - Poupin, Joseph; Corbari, Laure (Zootaxa, 2016)
A preliminary assessment of the deep-sea Decapoda is proposed for Guadeloupe Island based solely on high definition macro photographs taken during the KARUBENTHOS 2015 Expedition to the Island (R/V Antea, 7–29 June 2015). Overall, 190 species are recognized, several of which are depicted with their fresh color for the first time. Previous records in the Lesser Antilles are documented and the geographic distribution of the species in these Islands is given. The historical contribution of the steamer Blake (1878–1879) in the Lesser Antilles is emphasized. All species inventoried during KARUBENTHOS 2015 were already reported in the western Atlantic but 34 of them are new records for the Lesser Antilles and 116 are reported for the first time from Guadeloupe Island. This preliminary inventory is estimated to include about 38% of the deep-sea Decapoda potentially occurring around Guadeloupe Island.